"Branded, biased and it wants to sell a product": typical ad representations influence the effect of ad recognition: a mixed-method research. Issue 1 (2nd January 2020) - Buvár, Ágnes; Orosz, Gábor
Abstract: In the present two-study mixed-method research, we aimed to explore how different ad representation dimensions influence the recognition of new advertising formats. Furthermore, we also investigated the effect of ad recognition on ad and brand liking. In line with the past applications of schema theory to advertising (Evans and Park 2015 ), as well as categorization theories, we found in both studies that ad representation dimensions influence ad recognition of new advertising formats, especially when the relevant feature is present in the ad. Ad representation dimensions such as branded, biased or selling facilitated ad recognition, while informative had a negative effect on ad recognition. The sponsored journal article represented an exception as both branded and biased representations hindered ad recognition. Furthermore, the effect of ad recognition on ad and brand liking varied across the tested messages. Theoretical and practical implications have been formulated. Future research might consider to further explore the effect of ad schemas on advertising and brand attitudes.